(Re)constructing Homelands Between Precarity and Intentionality: Syrian Armenians in Armenia - Sossie Kasbarian (Mashriq & Mahjar)
Syrian refugees from the war which has been waging since 2011 now number more than 6.4 million. Of these, an estimated 24,000 Syrians of ethnic Armenian origin have arrived in the Republic of Armenia since 2011. Government sources estimate the number of those who have stayed to number around 14,000. Some have moved to other destinations perceived to hold better prospects, whether temporarily or with a view to stay permanently; others have returned to rebuild their lives in Syria. In mapping these multidirectional movements, it is apparent that Syrian Armenians’ encounter with Armenia is a process of continuous negotiation—Armenia is alternately a site of refuge, a historic or potential homeland, and a temporary transit. While previous studies have acknowledged the economic, social, and political challenges of settling in Armenia, the 2020 war in Artsakh/Nagorno Karabakh and its continuing reverberations at both the local and the wider geopolitical levels add a layer of critical precarity that is qualitatively different. This article argues that the 2020 war and its continuing violences have rendered Armenia a precarious homeland for Syrian Armenian refugees. Such precarity potentially jeopardizes the intentionality of many Syrian Armenians to stay in Armenia.